Newer chalcone scaffolds with reactive functional groups: Process, spectral and single crystal XRD studies - Borane, Niteen; Deshmukh, Amar Ghanshyam; Oza, Nidhi Harnesh; Boddula, Rajamouli; Patel, Paresh Narayan (European Journal of Chemistry, 2023)
Chalcones are versatile scaffolds for the synthesis of various heterocyclic systems with commercial utility. This work describes the synthesis of five novel chalcone derivatives. Syntheses were performed by a simple one-pot, straightforward Claisen-Schmidt condensation catalyzed with pyrrolidine and KOH. The chalcones were prepared by condensation of 4-formylbenzonitrile with different aromatic ketones at room temperature. The structures of all compounds have been investigated by FT-IR, NMR, and HR-MS spectroscopy. In addition, one chalcone structure was characterized by single-crystal XRD study. Crystal data for C21H15NO2 (Ch2): monoclinic, space group P21/c (no. 14), a = 6.5694(3) Å, b = 33.2697(15) Å, c = 7.4516(4) Å, β = 97.563(2)°, V = 1614.47(14) Å3, Z = 4, T = 293(2) K, μ(MoKα) = 0.083 mm-1, Dcalc = 1.289 g/cm3, 16000 reflections measured (4.898° ≤ 2Θ ≤ 49.99°), 2822 unique (Rint = 0.0249, Rsigma = 0.0196) which were used in all calculations. The final R1 was 0.0484 (I > 2σ(I)) and wR2 was 0.1257 (all data). The absorption maxima of all novel products were evaluated by UV-visible spectroscopy. These well-established structures of all newly prepared chalcone scaffolds with reactive functional groups (i.e. nitrile and 2-propenone) can be exploited as a crucial intermediate in the synthesis of new heterocyclic scaffolds with fluorescence and other applications.